2019
DOI: 10.3390/atmos10070362
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Observation of Atmospheric Speciated Mercury during 2007–2018 at Cape Hedo, Okinawa, Japan

Abstract: The concentrations of atmospheric gaseous elemental mercury (GEM), gaseous oxidized mercury (GOM), and particle-bound mercury (particles with diameter smaller than 2.5 μm; PBM2.5) were continuously observed for a period of over 10 years at Cape Hedo, located on the north edge of Okinawa Island on the border of the East China Sea and the Pacific Ocean. Regional or global scale mercury (Hg) pollution affects their concentrations because no local stationary emission sources of Hg exist near the observation site. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 56 publications
(78 reference statements)
2
7
0
Order By: Relevance
“…An upward trend was surprising because manual mercury measurements at the same site in 1995 -2004 showed a downward trend. Downward trends of atmospheric mercury concentrations and of mercury wet deposition have also been reported for many sites in the northern hemisphere (Temme et al, 2007;Cole et al, 2014;Steffen et al, 2015;Weigelt et al, 2015;Weiss-Penzias et al, 2016;Marumoto et al, 2019) but Cape Point has been the only station in the southern hemisphere with a long enough mercury concentration record to calculate trends. The northern hemispheric downward trend has been attributed to decreasing emissions from the North Atlantic Ocean due to decreasing mercury concentrations in subsurface water (Soerensen et al, 2012) and more recently to decreasing global anthropogenic emissions mainly due to the decline of mercury release from commercial products and the changes of Hg 0 /Hg 2+ speciation in flue gas of coal-fired utilities after implementation of NOx and SO2 emission controls (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 69%
“…An upward trend was surprising because manual mercury measurements at the same site in 1995 -2004 showed a downward trend. Downward trends of atmospheric mercury concentrations and of mercury wet deposition have also been reported for many sites in the northern hemisphere (Temme et al, 2007;Cole et al, 2014;Steffen et al, 2015;Weigelt et al, 2015;Weiss-Penzias et al, 2016;Marumoto et al, 2019) but Cape Point has been the only station in the southern hemisphere with a long enough mercury concentration record to calculate trends. The northern hemispheric downward trend has been attributed to decreasing emissions from the North Atlantic Ocean due to decreasing mercury concentrations in subsurface water (Soerensen et al, 2012) and more recently to decreasing global anthropogenic emissions mainly due to the decline of mercury release from commercial products and the changes of Hg 0 /Hg 2+ speciation in flue gas of coal-fired utilities after implementation of NOx and SO2 emission controls (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 69%
“…Many studies show that ambient atmospheric Hg concentrations are declining (Martin et al, 2017;Marumoto et al, 2019;Navrátil et al, 2018;Zhang et al, 2016), though this appears not to be the case universally (Fu et al, 2015;Martin et al, 2017). Declining Hg will, in general, mean declining ecosystem impacts, but the timing and spatial aspects of those changes are uncertain because atmospheric impacts to the surface are complex.…”
Section: Advances In Understanding Atmosphere Chemistry and Inputs To Ecosystemsmentioning
confidence: 99%
“…Lulin, Taiwan since measurements began in 2006. Marumoto et al [35] measured decreasing GEM trends at Cape Hedo, Okinawa, Japan, but no significant annual trends in either GOM or PBM 2.5 . For deposition, Fu et al [10] reported recent wet deposition rates in China from measurements and other studies.…”
Section: Introductionmentioning
confidence: 97%